The equation of the perpendicular through the point (4,-6) is
.
Given the equation of the original line:
y + 1 = -3( x - 5)
Using the point-slope formula, y - y₁ = m( x - x₁ ), the slope of the original line is:
Slope m = -3
The slope of the perpendicular line is a negative reciprocal of the original slope.
The slope of the perpendicular line = 1/3.
Plug the slope m = 1/3 and point (4,-6) into the point-slope form and simplify:
y - y₁ = m( x - x₁ )
![y - (-6) = (1)/(3)( x - 4 ) \\y + 6 = (1)/(3)( x - 4 )](https://img.qammunity.org/2020/formulas/mathematics/college/6nl7i6qwg0ctk7vvxng96rxqhzt4dnfe1v.png)
Therefore, the equation of the perpendicular line is
.